2010
DOI: 10.1080/00288306.2010.505944
|View full text |Cite
|
Sign up to set email alerts
|

A mid-Pliocene shearwater skull (Aves: Procellariidae:Puffinus) from the Taihape Mudstone, central North Island, New Zealand

Abstract: A fossil skull of Puffinus sp. (Aves: Procellariidae), 85 mm long, is reported from the mid-Pliocene Taihape Mudstone (3.220Á3.110 Ma; Waipipian Stage) at Mataroa, near Taihape, central North Island, New Zealand. This is the first described evidence for Puffinus in New Zealand's pre-Pleistocene fossil record. The skull belonged to a shearwater of a species close in skull size and proportions to the present-day wedge-tailed shearwater (P. pacificus). It could be conspecific with P. pacificus, or of the ancestra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Actually, using the same value as Austin et al, and only sequences from cytb , we found a divergence time of 2.2–3.8 My, thus very close to Austin et al Many substitution rates for both Mt DNA markers were proposed for petrels, ranging from 0.19%/My (Pacheco et al, 2011) to 1.544%/My (Pereira & Baker, 2006) for cox1 , and from 0.18%/My (Pacheco et al, 2011) to 0.88–0.92%/My (Nunn & Stanley, 1998; the latter rate was used by Austin et al), 1.022%/My (Pereira & Baker, 2006), and 1.89%/My (Weir & Schluter, 2008) for cytb . Using the lowest substitution rates (Pacheco et al, 2011) resulted in a divergence time between Atlantic and Indo‐Pacific lineages around 12.8 My ago (Supplementary Material ), an unlikely value given the presence of an ocean between the Americas before the Isthmus of Panama erected, despite the fact that Puffinus is dating back to the Oligocene (Henderson & Gill, 2010). Here, we used the substitution rates that were estimated in Nabholz et al (2016), as the most recent review.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, using the same value as Austin et al, and only sequences from cytb , we found a divergence time of 2.2–3.8 My, thus very close to Austin et al Many substitution rates for both Mt DNA markers were proposed for petrels, ranging from 0.19%/My (Pacheco et al, 2011) to 1.544%/My (Pereira & Baker, 2006) for cox1 , and from 0.18%/My (Pacheco et al, 2011) to 0.88–0.92%/My (Nunn & Stanley, 1998; the latter rate was used by Austin et al), 1.022%/My (Pereira & Baker, 2006), and 1.89%/My (Weir & Schluter, 2008) for cytb . Using the lowest substitution rates (Pacheco et al, 2011) resulted in a divergence time between Atlantic and Indo‐Pacific lineages around 12.8 My ago (Supplementary Material ), an unlikely value given the presence of an ocean between the Americas before the Isthmus of Panama erected, despite the fact that Puffinus is dating back to the Oligocene (Henderson & Gill, 2010). Here, we used the substitution rates that were estimated in Nabholz et al (2016), as the most recent review.…”
Section: Discussionmentioning
confidence: 99%
“…This latter parameter is probably a major contributor to the difference observed between our studies, since using the same value as Austin et al, and only sequences from cytb , we found a divergence time of 2.2-3.8 My, thus very close to Austin et al Many substitution rates for both Mt DNA markers were proposed for petrels, ranging from 0.19%/My (Pacheco et al 2011) to 1.544%/My (Pereira & Baker 2006) for cox1 , and from 0.18%/My (Pacheco et al 2011) to 0.88-0.92%/My (Nunn & Stanley 1998; the latter rate was used by Austin et al), 1.022%/My (Pereira & Baker 2006) and 1.89%/My (Weir & Schluter 2008) for cytb . Using lowest rates (Pacheco et al 2011) resulted in a divergence time between Atlantic and Indo-Pacific lineages around 12.8 My ago (Supplementary Material 10), an unlikely value given the presence of an ocean between the Americas before the Isthmus of Panama erected, despite the fact thatPuffinus is dating back to the Oligocene (Henderson & Gill 2010). Here we used the substitution rates that were estimated in Nabholz et al 2016, as the most recent review.…”
Section: Sequencing Artifacts Due To Mtdna Duplication and Uncertainties About Molecular Clock Ratesmentioning
confidence: 99%
“…A record of Pliocene 'Puffinus' from near Taihape, from similarly aged deposits as those that yielded A. buchananbrowni sp. nov., remains unnamed [35].…”
Section: Comparisons With Other Shearwater Fossilsmentioning
confidence: 99%